Pengaruh Pembiayaan Jual Beli (Murabahah), Pembiayaan Bagi Hasil (Mudharabah), Pembiayaan Bermasalah (NPF) Gross, Pembiayaan Bermasalah (NPF) Net terhadap Kinerja Keuangan (ROA) di Bank Syariah Mandiri (2011-2020) - Hasian Purba (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
The purpose of this study, among others, is to find out how the effect of buying and selling financing on the financial performance of Syariah Mandiri banks in 2011-2020. To find out how the influence of profit-sharing financing on the financial performance of Syariah Mandiri banks in 2011-2020. To find out how the effect of Gross non-performing financing on the financial performance of Syariah Mandiri banks in 2011-2020. To find out how the influence of non-performing financing Net on the financial performance of Bank Syariah Mandiri in 2011-2020. To find out how the influence of buying and selling financing, profit sharing, NPF Gross and NPF Net on the financial performance of Syariah Mandiri banks in 2011 - 2020. This study is associative, namely the research method carried out to find the relationship between one variable and another, as well as testing and use the truth of a problem or knowledge. The results of the study are Non-performing Financing, Sales and Purchase Financing, Gross Non-performing Financing (Npf) partially have no significant effect on financial performance while Non-Performing Financing (NPF) Net have a significant effect on financial performance. The regression of the Non-performing Financing, Buying and Selling Financing, Gross Non-performing Financing (NPF) and Net Non-performing Financing (NPF) variables do not simultaneously have a significant effect on Financial Performance.